2020
DOI: 10.1001/jamanetworkopen.2020.17271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Health Care Worker Burnout During the Coronavirus Disease 2019 (COVID-19) Pandemic in Japan

Abstract: with among the highest numbers of patients with COVID-19 in the country. We selected HCWs, including physicians, nurses, laboratory medical technologists, radiological technologists, and pharmacists, who worked in departments in which they had contact with patients with COVID-19, including emergency departments, general internal medicine departments, respiratory medicine departments, infectious disease departments, general wards, and intensive care units. An explanation of the sample size calculation appears i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
292
7
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(388 citation statements)
references
References 6 publications
37
292
7
13
Order By: Relevance
“…Female gender and higher workload were found to be positively associated with burnout in our study, this has been also reported by Matsue et al, who found that female gender, exposure to higher workload as well as the desire for appreciation were all signi cantly associated with burnout among healthcare workers during the current pandemic [42]. Despite that the logistic regression model in our study did not nd COVID-19 nancial incentives as a predicting factor of burnout, many physicians in our qualitative interviews have reported the need for a reliable acknowledgment to HCPs emotionally and nancially, which relates to Matsue et al nding of desire for appreciation.…”
Section: Discussionsupporting
confidence: 90%
“…Female gender and higher workload were found to be positively associated with burnout in our study, this has been also reported by Matsue et al, who found that female gender, exposure to higher workload as well as the desire for appreciation were all signi cantly associated with burnout among healthcare workers during the current pandemic [42]. Despite that the logistic regression model in our study did not nd COVID-19 nancial incentives as a predicting factor of burnout, many physicians in our qualitative interviews have reported the need for a reliable acknowledgment to HCPs emotionally and nancially, which relates to Matsue et al nding of desire for appreciation.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a lot of research is being done concerning other occupations such as health workers, teachers, etc. [5,[55][56][57][58][59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted outside the epidemic period, high levels of burnout have been reported among healthcare professionals both in our country and in the world (Erol et al, 2012;Kansoun et al, 2019). In the study of Matsuo et al (2020), where they investigated the prevalence of burnout in healthcare professionals during the COVID-19 outbreak in Japan with the participation of 488 healthcare professionals, the overall burnout prevalence was found to be 31.4% (98 out of 312). 59 (46.8%) of 126 nurses, 8 (36.4%) of 22 radiology technologists, and 7 (36.8%) of 19 pharmacists were experiencing burnout.…”
Section: Introductionmentioning
confidence: 97%